Langmuir‐Blodgett Assembly to order Nanoparticles and Colloidal Objects (British Journal of Multidisciplinary and Advanced Studies, 2022)
Bottom-up assembly of nanoparticles and colloidal objects pose a formidable challenge when processing devices. Speed, compatibility with various materials, defect tolerance and cost effectiveness are among the desired properties of a suitable nanoscale assembly process. In this regard, the Langmuir‐Blodgett (LB) technique is a highly sought-after candidate which aids in arranging a large number of nanostructures on solid surfaces. This mini-review aims to provide a concise account on the LB technique and four distinct ways of how it allows to assemble systems made of nanoparticles and colloidal objects: namely, close-packed nanoparticle superlattices by compression, micrometer scale nanoparticle fingering patterns by dip coating, single nanoparticle lines by stick-slip deposition and one-step patterning of aligned nanowire arrays.